Meta-Analisis Pengaruh Model Pembelajaran Kooperatif Tipe Example Non Example Terhadap Hasil Belajar IPA - Lailia Novitasari; Nyoto Harjono (JANACITTA, 2019)
The purpose of this research is to re-analyze the effect of Example Non Example model increasing the learning outcome in science subject. The reaseach method was meta-analysis.  In the first steps of the research is formulating research problem continued to colleting data on the test wich has been traced through the Google Scholar and repository of electronic journal. From the research,  getting5 articels from jurnals, 5  minithesis from relevan repository. The data were analyzed using qualitative descrpitive analysis. From the analysis result showed that Example Non Example learning model could improve student’s learning outcomes from the lowest percentage scor 12,08% to the highest 94,94% and the mean was 32,98%.